Phenotypic characterization, genetic analysis and antibiotic sensitivity of Aeromonas hydrophila isolates causing dropsy in cultured Labeo rohita from Punjab, Pakistan - Fatima Sughra; Muhammad Hafeez-ur-Rehman; Farzana Abbas; Imran Altaf; Saira Razzaq; Sidra Kanwal; Muhammad Inayat; Iqra Anwer; Muhammad Akram (Journal of Fisheries, 2022)
Motile Aeromonas septicemia (MAS) is a common freshwater fish disease and major threat to the aquaculture in Pakistan. The present study was carried out on suspected fish samples to isolate and characterize local strains of Aeromonas hydrophila, a key pathogen responsible for the said disease in aquacultured fishes. A total of ninety suspected fish specimens were collected from fish farms in Kasur, Okara and Gujranwala districts of Punjab, Pakistan from June 2018 to April 2019. The specimens were processed and A. hydrophila strains were isolated. The primary identification of sixty seven isolates were verified by colony morphology, microscopy and phenotypic characterization with ten biochemical reactions. The A. hydrophila strains of test samples were molecularly characterized by polymerase chain reaction (PCR) using 16S rRNA at desired size of 356bp. The PCR amplified product was subjected to DNA sequencing and phylogenetic analysis showed homology with related strains of Aeromonas spp. By antibiotic sensitivity test, the isolates were checked for nine antibiotics in which the pathogen was sensitive to four and resistant to five drugs. Results of genetic analysis confirmed strains as A. hydrophila which are useful to take preventive measures against the said disease.